2018
DOI: 10.1080/1331677x.2018.1486722
|View full text |Cite
|
Sign up to set email alerts
|

Corporate sustainability disclosure and market valuation in a Middle Eastern Nation: evidence from listed firms on the Tehran Stock Exchange: sensitive industries versus non-sensitive industries

Abstract: This article has received the considerable critical attention that seeking to enhance sustainability disclosure may essentially make progress firms' market valuation. It aims to provide the corporate sustainability disclosure level organized according to the '7 þ 1', seven core subjects of the International Organization for Standardization (ISO) 26000 and the energy disclosure items, then set out to assess the effectiveness of sustainability reporting on the listed firms' market valuation during the period 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 97 publications
2
19
0
Order By: Relevance
“…It will implicate the stock returns increase. The results of this research are supported by Mohammadi et al (2018) that said the overall extent of sustainability disclosure arranged in accordance with the low rate of sustainability reporting for listed firms in Tehran Stock Exchange. It was also found that sensitive firms have a higher level of corporate sustainability disclosure than other firms.…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…It will implicate the stock returns increase. The results of this research are supported by Mohammadi et al (2018) that said the overall extent of sustainability disclosure arranged in accordance with the low rate of sustainability reporting for listed firms in Tehran Stock Exchange. It was also found that sensitive firms have a higher level of corporate sustainability disclosure than other firms.…”
Section: Methodssupporting
confidence: 68%
“…Weir (2010) showed that the stock market reacts negatively to news about the environmental behavior of firms. Mohammadi et al (2018) said the overall extent of sustainability disclosure arranged in accordance with the low rate of sustainability reporting for listed firms in Tehran Stock Exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetarian consumers belong to the group of consumers who are aware of their surroundings and seek to build a model in which economic activity goes as far as possible not to harm the available natural and biological resources. In the search for a more sustainable and environmentally-friendly system, many stakeholders have the power and the responsibility to carry out this transformation in pursuit of the common good [88]. This is so because achieving more sustainable practices requires the coordination and support of all parties involved in the production and consumption processes [ Figure 3].…”
Section: Ecological Companies and Productsmentioning
confidence: 99%
“…An enterprise's sustainability depends on small businesses and their surroundings to co-create value for customers [18]. Firms acting in environmentally sensitive industries with sustainability reporting have higher market valuations [19]. Third, policy and public support are needed for sustainability transitions [20].…”
Section: Sustainability and Intergenerational Evolution Of Industrialmentioning
confidence: 99%